If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 14 = 13 + -26m Reorder the terms: 14 + 3m = 13 + -26m Solving 14 + 3m = 13 + -26m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '26m' to each side of the equation. 14 + 3m + 26m = 13 + -26m + 26m Combine like terms: 3m + 26m = 29m 14 + 29m = 13 + -26m + 26m Combine like terms: -26m + 26m = 0 14 + 29m = 13 + 0 14 + 29m = 13 Add '-14' to each side of the equation. 14 + -14 + 29m = 13 + -14 Combine like terms: 14 + -14 = 0 0 + 29m = 13 + -14 29m = 13 + -14 Combine like terms: 13 + -14 = -1 29m = -1 Divide each side by '29'. m = -0.03448275862 Simplifying m = -0.03448275862
| 2/3/3/7 | | -3n+6+7n=6 | | -4(5x-3)=-108 | | 9/2+1/3t=7 | | 24/5/6 | | y=1/4(4)-4 | | 3+FISH= | | 4x+18-3x=-2-11 | | 1/7(2x-5)=3 | | 100(0.06x+0.10(2x+24000))=100(23980) | | 6y+3=8y-5 | | (a^4+3a^3+2a^2)/4a^2 | | 100(0.06x+0.10(2x+24000))= | | 0.71+0.23t=2.58t-0.23 | | (3-4i)/(5+3i)=0 | | 6+5=5+8+2 | | 3(3-x)-19=17x-5(2+4x) | | (3-4i)/(5+3i) | | 4x-.5=x+10 | | 18*6= | | 5(x-6)+2=7(x+2)-6 | | 5+10c=10c | | .51x-5.04=-.09x | | 3/4+x=x+12 | | 48-x=4(7x) | | 4x-17=2x-1 | | y=4(-1)+16 | | 48-x=4x(7x) | | 48*6= | | 2+12x=3(4x+2) | | 3(3x-4)-4=3(x-4)+26 | | 2/5(x-10)=-12 |